Influence of build orientation and aging on corrosion behaviour of 18Ni300 maraging steel produced via Powder Bed Fusion using Laser Beam (PBF-LB) - Vishwakarma J.; Chattopadhyay K.; Srinivas N.C.S. (My University, 2025)
Conventional maraging steel corrodes uniformly but additive manufactured (AM) maraging steel can corrode differently, depending upon the angle of exposure of build layers to the corrosive media. The primary objective of this investigation is to examine the effect of build orientation and solution aging treatment (HT) on the corrosion behaviour of the AM maraging steel and to compare with that produced through the conventional route of casting and hot rolling. In this investigation, corrosion behaviour of maraging steel samples produced by Powder Bed Fusion using Laser Beam (PBF-LB), with different build orientations of 0°, 45°, and 90°, was investigated in a 3.5% NaCl solution. Corrosion resistance of the as-built (AB) samples was found to increase with decrease in the angle of inclination and related to structural heterogeneity and grain boundary density. However, corrosion resistance of the AB samples was decreased following heat treatment (solutioning and aging) and was controlled by precipitation of intermetallic phases and reversed austenite generation. While there was dominance of protective oxide layer of TiO2 in the AB and conventional sample, this oxide layer was not observed on the heat treated (HT) samples. Further, a marked difference was observed in pitting corrosion of the AB and HT samples. © 2023 Elsevier Ltd